2007
DOI: 10.1149/1.2761526
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Interface Analysis of Ti∕Ni∕Ti∕Au Ohmic Contacts on n-Type 6H–SiC

Abstract: We present the results of Ti/Ni/Ti/Au multilayer ohmic contacts on n-type 6H-SiC and their interface analysis. The as-deposited contacts show rectifying behavior and, with the increase in annealing temperature, they gradually transform to high-quality ohmic contacts exhibiting linear current-voltage characteristics. The interface evolution was analyzed through glancing angle X-ray diffraction, Auger electron spectroscopy, and atomic force microscopy. The TiSi 2 and Ni 2 Si formed at the interfaces during the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Linchao et al have also identified a significant reduction in resistance of Ni/Ti/Ni contacts to n-SiC after annealing at 1000 °C which corresponded to a complete indiffusion of Ni into the SiC [4]. Previous work has shown that in Ni/Ti contacts to SiC, the formation of Ni 2 Si during high temperature annealing (~1000 °C) was essential in obtaining ohmic behaviour [4,5]. A reduction in contact resistance during annealed of these contacts has also been attributed to the formation of TiSi 2 by the reaction of Ti with SiC [3,6].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Linchao et al have also identified a significant reduction in resistance of Ni/Ti/Ni contacts to n-SiC after annealing at 1000 °C which corresponded to a complete indiffusion of Ni into the SiC [4]. Previous work has shown that in Ni/Ti contacts to SiC, the formation of Ni 2 Si during high temperature annealing (~1000 °C) was essential in obtaining ohmic behaviour [4,5]. A reduction in contact resistance during annealed of these contacts has also been attributed to the formation of TiSi 2 by the reaction of Ti with SiC [3,6].…”
Section: Resultsmentioning
confidence: 99%
“…A reduction in contact resistance during annealed of these contacts has also been attributed to the formation of TiSi 2 by the reaction of Ti with SiC [3,6]. In Ni/Ti contacts, the Ti has been shown to react with excess carbon to form TiC [3][4][5]. Evidently, from the present results, a large amount of indiffusion of interfacial layers at 1000 °C was required in order to obtain the necessary reactions for a lowering in ρc For samples which were implanted at the higher dose of 1 x 10 15 ions/cm 2 , a similar order of magnitude decrease in ρc was measured after annealing at 1000 °C although with higher values of ρc ~ 2-4 x 10 -5 Ω.cm 2 than at the lower implant doses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 4 shows the room temperature I-V characteristics of the fabricated p-Cu:ZnO/n-6H:SiC structure, exhibiting fairly good rectifying diodelike behavior with a threshold voltage of about 1 V. In order to overcome the ohmic metallization problem posed by the n-6H:SiC, the multilayered metallzation scheme proposed by Basak and Mahanty [34] has been used. The insets in figure 4 correspond to the I-V curves of the p-p and n-n contacts, showing the ohmic behavior of the Au/Ni/Au/Cu:ZnO and Au/Ti/Ni/Ti/6H:SiC multilayered metallization on both the p and n sides of the device, respectively [24]. The electroluminescence spectra of p-Cu:ZnO/n-6H:SiC LED, shown in figure 5, exhibit the main blue emission peak centered at 2.59 eV (= 478 nm) and a broad green emission at 2.38 eV (= 520 nm) with no UV emission, and matches well with the PL spectra.…”
Section: Resultsmentioning
confidence: 99%
“…The n-type electrodes were thermally annealed at 900 • C in N 2 environment for 5 min [24], and p-type electrodes were thermally annealed in air at 900 • C for 5 min, respectively. The photoluminescence (PL) measurements by using He-Cd excitation source (λ = 325 nm, 25 mW) and electroluminescence (EL) measurements were taken at room temperature.…”
Section: Methodsmentioning
confidence: 99%